The inclusion of Bioethics as a Transverse Axis in the EBR - Ruiz Alvarado, José Rogelio (2019)
The Peruvian society, faced situations in which people express humiliation for life without any remorse; It is possible to discover the vast majority of times, the authors of these harmful acts come from dysfunctional homes, an atmosphere of family violence, and even many of them did not finish the basic regular education, we are referring to the process that requires commitment and delivery, not only on the part of teachers, but also of parents or guardians, who will reinforce at home what you teach your children or wards in educational institutions. The important role played by education, it is not only in the aspect of scientific and technological discoveries and advances, but human quality of people, to its ethical principles, ethical and moral values that are learned during the school. The scope of bioethics has amplified, today, includes not only the medical ethics, environmental ethics, debates about the rights of future generations, sustainable development, etc. To include the transverse axis of the bioethics education, they will have to take into account the part that makes up the essence of bioethics, its principles and the humanisation of education.